Traditional Birth Attendants’ Practice Encounters: Experiences from Northern Nigeria - Yahaya Jafaru; Aisha Abdullahi Magaji; Maryam Kabiru Haruna (International Journal of Nursing and Health Services (IJNHS), 2026)
Background: The utilization of Traditional Birth Attendants (TBAs) is one of the patient-level factors that are common in causing maternal mortality. The TBAs are deficient in the ability to identify or manage birth complications such as postpartum haemorrhage and birth asphyxia. However, training and retraining are given to TBAs without ascertaining their practice needs. The aim of the study was to explore the difficult situations the Traditional Birth Attendants encountered during their practice. Methods: The study employed a descriptive phenomenological research design. The population of the study consisted of TBAs currently practicing in Birnin Kebbi Metropolis. A purposive sampling strategy was employed to select twelve veterans TBAs for the study. An in-depth interview was used for data collection. One-on-one interviews were conducted by the researchers with each participant TBA. Giorgi’s descriptive phenomenological method was used for the analysis. four themes that emerged from this study conducted through in-depth interview. Results: The four themes that emerged from this study are difficulties in conducting labour, retained placenta, umbilical cord issues, and method of identifying abnormal labour. Conclusion: The identified difficulties encountered by TBAs are crucial. These are difficulties that could lead to serious maternal and neonatal health issues. Understanding these difficulties underscores the importance of training TBAs.